miR-146a rs2910164 polymorphism might be associated with coronary artery disease risk in Asians - Zhou, H-Y.; Wei, Q.; Shi, X-D; Cao, H-Y.; Qin, L. (Cellular and Molecular Biology, 2017)
Recently, several studies reported the association between miR-146a rs2910164 polymorphism and coronary artery disease (CAD) risk. However, the results were inconclusive. We therefore did a meta-analysis to investigate this association. Electronic databases, including PubMed, EMBASE, and China National Knowledge Infrastructure (CNKI) databases, were searched. The strength of association was assessed by calculating odds ratios (OR) and 95% confidence interval (CI). Five eligible studies included in this meta-analysis. The total sample size of this meta-analysis was 1565 cases and 1541 controls. We found that miR-146a rs2910164 polymorphism was significantly associated with an increased CAD risk (OR = 1.19; 95% CI 1.07 – 1.32; P = 0.002). In the subgroup analysis by race, miR-146a rs2910164 polymorphism was significantly associated with an increased CAD risk in Asians (OR = 1.18; 95% CI 1.04 – 1.33; P = 0.008). However, we did not find significant result in Caucasians (OR = 1.22; 95% CI 0.86 – 1.74; P = 0.25). In the subgroup analysis by age, we found that miR-146a rs2910164 polymorphism increased CAD risk in old population (OR = 1.22; 95% CI 1.09 – 1.38; P = 0.0008). In conclusion, this meta-analysis found that miR-146a rs2910164 polymorphism was significantly associated with CAD risk.